FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN ULANG AKSEPTOR KB SUNTIK 3 BULAN PADA MASA PANDEMI COVID-19 DI PUSKESMAS BRUNO - Zuliyanti, Nurma Ika; Andriyani, Eka (Jurnal Komunikasi Kesehatan, 2022)
Based on data obtained from the kb visit register book at the Bruno Health Center which visited 119 acceptors, 45 acceptors were obtained who did not re-visit according to the schedule and 84 acceptors of injectable KB 3 months made re-visits as scheduled. The purpose of the study was to determine the factors related to the 3-month injection kb acceptor re-visit during the Covid-19 pandemic. This research method is an analytical survey with a Cross Sectional approach. The population in this study was all acceptors of 3-month injectable birth control at Bruno's Health Center. Sampling using accidental sampling technique. The research time is from March to May 2022. Data analysis using chi-square test. Where the results show that there is a relationship if (p<0.05) for the knowledge variable (p value 0.033). There is no relationship between age (p value 0.951), education (p value 0.458) and income (p value 0.449).